IMPACT OF IRRIGATION MANAGEMENT PRACTICES AND WATER QUALITY ON MAIZE PRODUCTION AND WATER USE EFFICIENCY - M. Irfan; M. Arshad; A. Shakoor; L. Anjum (Journal of Animal and Plant Sciences, 2014)
In order to study the effect of irrigation methods and water quality on maize yield and water use efficiency, the research work was carried out at Postgraduate Agricultural Research Station (PARS), Faisalabad, Pakistan. Six treatments i.e. T1D (Drip irrigation with good quality water), T2D (Drip irrigation with marginal quality water), T3D (Drip irrigation with poor quality water), T1R.B (Raised bed irrigation with good quality water), T2RB (Raised bed irrigation with marginal quality water) and T3RB (Raised bed irrigation with poor quality water) with three replication of each treatment were used. Field data regarding germination rate, plant height, crop yield and the water use efficiency were collected and the results were analyzed. It was found that irrigation method and water quality both affected the plant height, germination rate, maize production and the water use efficiency. It was concluded that the maize crop yield (8487kg/ha) and water use efficiency (13.92kg/ha-mm) was high in T1D. The crop yield in T2D, T3D, T1RB, T2RB and T3RB treatment were reduced by 5, 12, 19, 29 and 37%, respectively. It was recommended that drip irrigation would be adopted where groundwater quality is marginal to poor quality to get high crop production and water use efficiency.
Keywords: `Drip irrigation; water use efficiency; raised- bed; CROPWAT model